Advances in Understanding the Effects of Erythropoietin on Renal Fibrosis - Zhang, Yangyang; Zhu, Xiaoyu; Huang, Xiu; Wei, Xuejiao; Zhao, Dan; Jiang, Lili; Zhao, Xiaoxia; Du, Yujun (Frontiers in Medicine, 2020)
Renal fibrosis is the common manifestation of the pathogenesis of end-stage renal disease that results from different types of renal insult, and is a hallmark of chronic kidney disease (CKD). The main pathologic characteristics of renal fibrosis are renal interstitial fibroblast hyperplasia and the aberrant and excessive deposition of extracellular matrix, pathologies that lead to the destruction of normal renal tubules and interstitial structures. However, the biological significance of fibrosis during the progression of CKD is not clear, and there are no approved clinical treatments for delaying or reversing renal fibrosis. Studies of the mechanism of renal fibrosis and of potential measures of prevention and treatment have focused on erythropoietin (EPO), a hormone best known as a regulator of red blood cell production. These recent studies have found that EPO may also provide efficient protection against renal fibrosis. Future therapeutic approaches using EPO offer new hope for patients with CKD. The aim of the present review is to briefly discuss the role of EPO in renal fibrosis, to identify its possible mechanisms in preventing renal fibrosis, and to provide novel ideas for the use of EPO in future treatments of renal fibrosis.